2013
DOI: 10.5713/ajas.2012.12513
|View full text |Cite
|
Sign up to set email alerts
|

Treated Olive Cake as a Non-forage Fiber Source for Growing Awassi Lambs: Effects on Nutrient Intake, Rumen and Urine pH, Performance, and Carcass Yield

Abstract: The objective of this study was to investigate the effects of partial replacement of wheat hay with sun-dried (SOC) or acid-treated SOC (ASOC) olive cake on nutrient intake and performance of Awassi lambs. An additional objective was to study the effects of acid treatment of olive cake (OC) on its chemical composition and nutritive value. On DM basis, sun-drying of OC did not dramatically affect its chemical composition. On the other hand, treating SOC with phosphoric acid decreased (p<0.05) SOC contents of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
30
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 23 publications
12
30
2
Order By: Relevance
“…Results are in agreement with Hadjipanayiotou (1999a, b). Both D3 and D4 diets contained relatively similar content of DM, CP, NDF, ADF, ADL and condensed tannins as reported by Awawdeh and Obeidat (2013) and Gomaa et al (2016). The allzyme SSF addition decreased the olive cake NDF contents that probably due to breaking off gross linkage between lignin and cell wall component and solubilizing of cell wall contents (mainly hemicelluloses).…”
Section: Chemical Compositionsupporting
confidence: 55%
See 1 more Smart Citation
“…Results are in agreement with Hadjipanayiotou (1999a, b). Both D3 and D4 diets contained relatively similar content of DM, CP, NDF, ADF, ADL and condensed tannins as reported by Awawdeh and Obeidat (2013) and Gomaa et al (2016). The allzyme SSF addition decreased the olive cake NDF contents that probably due to breaking off gross linkage between lignin and cell wall component and solubilizing of cell wall contents (mainly hemicelluloses).…”
Section: Chemical Compositionsupporting
confidence: 55%
“…Most of the tests recommended the inclusion of 8 to 10 percent of molasses with the olive cake. On the other hand, Awawdeh and Obeidat (2013) reported no effects of dietary treatments on lambs intake when they fed a diet containing olive cake. Findings are in agreement with the results of Bedford and Partridge, (2011).…”
Section: Feed Intakementioning
confidence: 96%
“…These results are in line with recent findings showing that the initial live weight, final live weight, and feed intake of lambs were not affected by olive pomace supplementation (5,9,11). However, Awawdeh and Obeidat (23) reported that the inclusion of sun dried olive pomace in the lamb's diet as a substitute for 10% of wheat hay increased the growth rate and total body weight gain. On the other hand, Tufarelli et al (24) found that lambs consuming oat hay replaced with 20% partially destoned exhausted olive pomace had lower final body weight (25.5 kg) and daily gain (178 g/ day) compared to control animals (26 kg and 198 g/day, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…Although differences present between the type (crude, pelleted, de-stoned, acid-treated, etc. ), dietary inclusion of crude olive cake (OC) up to 100 g/kg was fairly safe without negative effects on lamb performance (Omar et al 2012;Awawdeh and Obeidat 2013;Tufarelli et al 2013). Previous studies demonstrate that sesame meal (SM) can be included in lamb diets at 80-200 g/kg without detrimental effects on performance (Omar 2002;Obeidat et al 2009;Hassan et al 2013).…”
Section: Introductionmentioning
confidence: 99%